The clinical effect of feedforward control nursing combined with methylphenidate sustained-release tablets on children with attention deficit hyperactivity disorder - Zou, Xiao (CNS spectrums, 2023)
BackgroundAttention Deficit Hyperactivity Disorder (ADHD) is a common psychological disorder in childhood, also known as child hyperactivity disorder. Its clinical manifestations mainly include excessive activity, inattention, impulsivity, irritability, etc. If the intervention is not carried out in time, it may lead to serious psychological, behavioral, social, learning, or other issues in children, affecting their normal social life. Although drug treatment can improve the symptoms of some ADHD patients, drug treatment alone may cause persistent residual symptoms, addiction and adverse reactions. Feedforward control nursing is an active intervention mode. It realizes the control purpose by controlling variables, plays the role of preventing problems before they occur and solving problems as early as possible. It can provide efficient and high-quality nursing for children. Therefore, our hospital conducted clinical treatment for children with attention deficit hyperactivity disorders through feedforward control nursing combined with methylphenidate sustained-release tablets, in order to provide reference value for the treatment intervention of children with attention deficit hyperactivity disorder.Subjects and Methods120 children with ADHD who were admitted to a psychiatric hospital in the same period were selected as the study subjects. The patients were randomly divided into the experimental group and the control group. The experimental group was given a treatment scheme of feedforward control nursing combined with methylphenidate sustained-release tablets, and the control group was given conventional drug treatment. Before the intervention, both groups were given methylphenidate hydrochloride sustained-release tablets for oral treatment. The initial dose of treatment was 19 mg per day, the maximum dose was 53 mg per day, and the intervention time was 3 months. The children were evaluated once a month with Abbreviated Symptom Questionnaire (ASQ). The lower the score, the better the intervention effect. The experimental data were analyzed by SPSS20.0 software.ResultsAfter 3-month intervention, the ASQ scores of the two groups were compared. The results were shown in Table 1. After the intervention, the scores of the experimental group at 1 month, 2 months and 3 months after the intervention were significantly lower than those before the intervention (P < 0.05), and the scores of the control group at 2 months and 3 months after the intervention were significantly lower than those before the intervention (P < 0.05). The scores of the two groups were compared. The scores of the two groups before the intervention were not statistically significant, but the scores of the experimental group at 1 month, 2 months and 3 months after the treatment were significantly lower than those of the control group (P < 0.05). Among them, * represents P < 0.05 compared with that before intervention, and # represents P < 0.05 compared between groups.Figure 1.Comparison of conners scale scores between the two groups before and after experimental group[Figure omitted. See PDF]ConclusionsDrug treatment alone can no longer meet the needs of patients, and the collaborative treatment of multiple therapies has become the current trend and research focus of this disease. In this study, feedforward control nursing combined with methylphenidate sustained-release tablets has a significant intervention effect on children with ADHD, which can improve the children’s sustained attention, effectively improve their behavioral ability and attention, and further improve the satisfaction of the children’s family members with nursing. It is worthy of promotion and application.